Trabalho infantil, educação e classe média na primeira república - Pimenta, Emelyn Mariana (2018)
The present research aims to investigate formal and non-formal child labor in the State of São Paulo, from 1900 to 1930, and to analyze the role played by the Middle Class in the fight against child labor. The first two decades of the 20th century embraced major changes. Among them, a newly established Republic, European immigration, educational reforms, the formation of the working class, the advance of industry in São Paulo and the expansion of the urban middle class stand out. The vast contingent of workers in the industries was formed by men, women and children. In addition to working in factories, children belonging to the less favored classes of society were employed in rural areas, especially during cotton and coffee planting and harvesting times. They also worked as newspaper deliverers, greengrocers, shoeshine workers, domestic helpers, bricklayers, among other activities. In this context, it is questioned what was the influence of some representatives of the middle class in the struggle for social issues on the agenda in the First Republic, especially with regard to child labor, as well as understanding what measures were used in favor of this cause. The studies showed that dissident groups from the upper middle class, such as doctors, lawyers, deputies, education intellectuals and education inspectors, stood out in the fight against child labour. However, most of them presented an ambiguous speech. At certain times, they contested child labor and sought to protect defenseless children who faced strenuous workdays. In others, they supported the use of child labor, with some recommendations. The contradictory behavior of the Middle Class resulted, in most cases, from the bonds of dependence maintained with the oligarchy, a situation that often impelled them to establish agreements that were more favorable to the bosses than in defense of children. (AU)